2000
DOI: 10.1034/j.1399-0039.2000.550205.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: a modifying influence of HLA class I genes in an HLA class II associated autoimmune disease

Abstract: Multiple sclerosis (MS) is a presumed autoimmune disease of the central nervous system, shown to be associated with the HLA class II haplotype DRB1*15,DQB1*06. Carrying the HLA class II haplotype DRB1*15,DQB1*06 increases the risk of MS by 3.6. By adopting a polymerase chain reaction (PCR)-based typing technique for HLA class I and class II genes, 200 Swedish MS patients and 210 Swedish healthy controls were analysed for their HLA alleles. Additional HLA class I alleles that increase and decrease the genetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
173
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(193 citation statements)
references
References 31 publications
(29 reference statements)
13
173
6
Order By: Relevance
“…The frequency of MOG-142L and HLA-A*02-positive individuals was significantly lower in cases than in controls, confirming the previously reported protective effect, 9,10,12,13 whereas the association with Cw*05 was not significant. To eliminate the possible confounding effect of linkage disequilibrium (LD) with HLA-DRB1*15, we performed the same analysis in DRB1*15-negative individuals.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The frequency of MOG-142L and HLA-A*02-positive individuals was significantly lower in cases than in controls, confirming the previously reported protective effect, 9,10,12,13 whereas the association with Cw*05 was not significant. To eliminate the possible confounding effect of linkage disequilibrium (LD) with HLA-DRB1*15, we performed the same analysis in DRB1*15-negative individuals.…”
Section: Resultssupporting
confidence: 85%
“…8 Conversely, other studies have detected the effect at least of one class I genetic factor independently of HLA-DRB1. Brynedal et al 9 confirmed in a Nordic cohort of 1084 MS patients and 1347 controls the results of a previous study performed in a smaller Swedish panel, 10 showing that HLA-A*02 is negatively associated with MS (OR ¼ 0.63, P ¼ 7 Â 10 À12 ). Yeo et al 11 analyzed over 1600 UK MS patients and 3600 controls and found that HLA-Cw*05 exerts an MS-protective effect (OR ¼ 0.49, 95% confidence intervals, CI ¼ 0.34-0.69, P ¼ 3.3 Â 10 À5 ) after excluding all individuals carrying DRB1 alleles associated with MS.…”
Section: Introductionmentioning
confidence: 63%
“…Furthermore, HLA class II-independent associations with HLA-A and -B have also been reported with other AIDs. In particular, HLA-A has been implicated in multiple sclerosis [34][35][36] and juvenile idiopathic arthritis, 37,38 whereas HLA-B is a well-known risk factor in ankylosing spondylitis 39 and has been implicated in systemic lupus erythematosus. 40 This raises the possibility that these genes represent susceptibility loci that are involved in common, autoimmune processes.…”
Section: Confirmation Of Mhc Class I Associationsmentioning
confidence: 99%
“…3 Within the MHC, the human leukocyte antigen (HLA) DRB1*1501-DRB5*0101-DQA1*0102-DQB1*0602 haplotype has a pre-eminent role, especially for populations of Northern European descent. [4][5][6][7] However, there is now robust, validated evidence that other variants within the MHC have independent roles in rendering individuals susceptible to MS, 8 and there is evidence for a role of the MHC in age at onset 9 and disease course. 10,11 Many studies have used clinical measures of severity to explore this aspect, but MRI-derived measures (such as brain atrophy and T 2 -weighted lesion volume or T2LV) appear to be more sensitive in capturing the course of disease, particularly in the early years after symptom onset.…”
Section: Introductionmentioning
confidence: 99%